N-Terminal methionine processing by the zinc-activated Plasmodium falciparum methionine aminopeptidase 1b - Calcagno, Sarah; Klein, Christian D. (Applied microbiology and biotechnology, 2016)
The methionine aminopeptidase 1b from Plasmodium falciparum (PfMetAP 1b) was cloned, expressed in Escherichia coli and characterized. Surprisingly, and in contrast to other methionine aminopeptidases (MetAPs) that require heavy-metal cofactors such as cobalt, the enzyme is reliably activated by zinc ions. Immobilization of the enzyme is possible by His-tag metal chelation to iminodiacetic acid-agarose and by covalent binding to chloroacetamido-hexyl-agarose. The covalently immobilized enzyme shows long-term stability, allowing a continuous, heterogenous processing of N-terminal methionines, for example, in recombinant proteins. Activation by zinc, instead of cobalt as for other MetAPs, avoids the introduction of heavy metals with toxicological liabilities and oxidative potential into biotechnological processes. The PfMetAP 1b therefore represents a useful tool for the enzymatic, posttranslational processing of recombinant proteins.
Gesehen am 28.04.2020